2015
DOI: 10.1038/aps.2014.129
|View full text |Cite
|
Sign up to set email alerts
|

The RAS-RAL axis in cancer: evidence for mutation-specific selectivity in non-small cell lung cancer

Abstract: Activating RAS mutations are common in human tumors. These mutations are often markers for resistance to therapy and subsequent poor prognosis. So far, targeting the RAF-MEK-ERK and PI3K-AKT signaling pathways downstream of RAS is the only promising approach in the treatment of cancer patients harboring RAS mutations. RAL GTPase, another downstream effector of RAS, is also considered as a therapeutic option for the treatment of RAS-mutant cancers. The RAL GTPase family comprises RALA and RALB, which can have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 83 publications
1
21
0
Order By: Relevance
“…Guin et al . found that RalA/RalB, as the downstream effector of RAS, might be important for tumor metastasis and invasion of NSCLC, but, however, their mechanisms remained unknown25. According to our results, we speculate that high expression of ENST00000439577 could up-regulate RCC2 expression, which may promote the activity of RalA, stimulating the growth and invasion of lung tumour cells.…”
Section: Discussionsupporting
confidence: 49%
“…Guin et al . found that RalA/RalB, as the downstream effector of RAS, might be important for tumor metastasis and invasion of NSCLC, but, however, their mechanisms remained unknown25. According to our results, we speculate that high expression of ENST00000439577 could up-regulate RCC2 expression, which may promote the activity of RalA, stimulating the growth and invasion of lung tumour cells.…”
Section: Discussionsupporting
confidence: 49%
“…Thus, contributing to cancer progression through adhesion, invasion and metastasis. Our study is an attempt to understand the role of RALBP1 in altering critical cellular activities, such as glycolysis, cellular migration, and invasion in OSCC …”
Section: Discussionmentioning
confidence: 99%
“…While RAS‐RAL axis has been investigated for non‐small cell lung carcinoma and other metastatic cancers very little of its role has been explored in oral cancers, which are also highly metastatic in nature. Through this study, we wish to ascertain (a) the role of RAL and in particular RALBP1 in promoting oral cancers (b) we wish to explore the mode of regulation of RALBP1.…”
Section: Introductionmentioning
confidence: 99%
“…Among the downstream RAS effectors, guanine exchange factors RAL (RAL A and RAL B GTPases) are also implicated in the transformation and invasion of pancreatic cancer cells. 37 , 38 Upon activation, RAL GTPase regulates numerous biological processes such as autophagy, cytokine activation, endocytosis, filopodia formation, membrane trafficking, and transcription. Abnormal regulation of these biological processes regulated by RAL can lead to proliferation, resisting cell death, cell invasion, and metastasis.…”
Section: Discussionmentioning
confidence: 99%